CONTEMPORARY POSSIBILITIES OF EXTRA NONSPECIFIC PROPHYLAXIS OF TICK BORN ENCEPHALITIS IN CHILDREN - N.V. Skripchenko; N.V. Morgatsky; G.P. Ivanova; O.A. Aksenov; M.V. Ivanova; V.V. Karasev; N.F. Pul'man; A.A. Vil'nits; E.A. Murina; E.Yu. Gorelik (Педиатрическая фармакология, 2007)
The present article contains new access to encephalitis. Results of different tactics of extra nonspecific prophylaxis of tick born used in 403 patients, who applied to hospitals for help after tick bite. Efficacy of seroprophy laxis in 361 child measured. Tactics of extra chemoprophylaxis with the help of antiviral preparation anaferon infantile was offered and its efficiency was proved in 82 children. Advantages of practical appliance of chemoprophylaxis to seroimmunity were validated.Key words: tick born encephalitis, children, prophylaxis, tick, anaferon